OEE, Literature Review Tinjauan Literatur Secara Sistematik Tentang Overall Equipment Effectiveness (OEE) di Industri Manufaktur dan Jasa: Tinjauan Literatur Secara Sistematik Tentang Overall Equipment Effectiveness (OEE) di Industri Manufaktur dan Jasa - Welly Atikno; Humiras Hardi Purba (Journal of Industrial and Engineering System, 2021)
Overall equipment effectiveness (OEE) is a performance evaluation method used to measure industrial equipment productivity as a key performance indicator. This literature study aims to identify, categorize, and synthesize research related to the application, study and analysis of OEE in various industrial fields. The literature review was carried out systematically, structured and directed manner on 35 journals in Asia in the last eight years. Covering OEE's core characteristics and synergizing the strengths of the improvement framework, this study will provide a systematic guide to OEE practitioners in implementing improvements that can be used to identify areas for future development and as a reference for further research.